Quelques clés du combat de François contre les abus, dix ans après le début de son pontificat - Farnós, Jordi Bertomeu (Nouvelle revue théologique, 2023)
Francis’ pontificate has been deeply marked by the crisis of sexual abuse in the Church. But this crisis has a history that is also juridical. The way in which crimes of pedophilia or sexual abuse by clerics have been dealt with has been marked by a form of post-conciliar anti-juridical naivety, which recent popes have sought to correct, starting with the 1983 Code and the importance assumed by the Congregation for the Doctrine of the Faith. The steps described here show Francis’ unequivocal determination to resolve this tragedy once and for all. But Francis has also ambitiously called on the Church as a whole to be a place of healthy and safe relationships for the most vulnerable of the faithful.